1972
DOI: 10.1126/science.176.4042.1414
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination at Power Plants: Impact on Phytoplankton Productivity

Abstract: Studies of the eflects of passage through a power plant on river phytoplankton have shown that chlorination depresses rates of photosynthesis and respiration to a much greater extent than does heating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…(2) According to the chronic toxicity of marine biological chlorine threshold line (2×10 -5 kg/m 3 ), the pollution zone which may have an impact on the marine life was obtained: in winter, the pollution zone was approximated to a band range of the length of 2900m, width of 500m, and the area of 0.752 km 2 , and in summer, the zone was approximated to the length of 1550m, width of 180m, and the area of 0.273km 2 . (3) The predicted result is the maximum increment of pollutant concentration in adverse hydrological condition, that is, the concentration of pollutant was selected as the maximum concentration at different time in the whole simulation period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) According to the chronic toxicity of marine biological chlorine threshold line (2×10 -5 kg/m 3 ), the pollution zone which may have an impact on the marine life was obtained: in winter, the pollution zone was approximated to a band range of the length of 2900m, width of 500m, and the area of 0.752 km 2 , and in summer, the zone was approximated to the length of 1550m, width of 180m, and the area of 0.273km 2 . (3) The predicted result is the maximum increment of pollutant concentration in adverse hydrological condition, that is, the concentration of pollutant was selected as the maximum concentration at different time in the whole simulation period.…”
Section: Discussionmentioning
confidence: 99%
“…When the cooling water containing chlorine discharged into nearby waters, it will affect the ecological environment of water. Brook found that when chlorine wastewater discharged into the ocean, it would inhibit phytoplankton photosynthesis and respiration by comparing the effects of temperature and water drainage on the phytoplankton [2].Ceng Jiangning carried out the analysis on the influence of residual chlorine on plankton, shellfish and fish, and draw the conclusion that the impact of chlorine in marine fish was more obvious [3].…”
Section: Introductionmentioning
confidence: 99%
“…Entrainment has frequently been found to result in a stimulation of photosynthetic activity during cold months while similar temperature increases during summer months resulted in a reduction of activity , MILLER et al, 1976, WARIN-NER and BREHMER, 1966, LAUER et al, 1974, KREH and DERWORT, 1976. I n some studies no temperature related stimulation of primary production was observed following entrainment ( MORGAN and STROSS, 1969, CARPENTER et al, 1972, BROOK and BAKER, 1972 or the reduced production levels noted occurred in association with high discharge temperatures (SMITH et al., 1974, FOX and MOYER, 1975, GURTZ and WEISS, 1974, FLEMER and SHERK, 1977. At these stations mechanical factors encountered during entrainment may have masked the expected stimulatory effect at sub-optimal temperatures and enhanced reduction a t temperatures which exceeded tolerance limits (MORGAN and STROSS, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…A stimulatory effect of condenser passage on photosynthetic activity has also been suggested ( STUART andSTANDFORD, 1978, LIND, 1975). The addition of chlorine to cooling waters has, however, been conclusively shown to severely inhibit phytoplankton primary production (Fox and MOYER, 1975, CARPENTER et al, 1972, BROOK and BAKER, 1972, FLEMER and SHERK, 1977, HAMILTON et aZ., 1970.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of entrainment on phytoplankton are variable and depend in part on the location and operating conditions of individual power plants (Warinner & Brehmer, I966;Hamilton, et al, 1970;Carpenter, et al, 1972;Brook & Baker, 1972;and Fox & Moyer, 1973). Most attention has been focused on the effects of a temperature rise over ambient temperature and chlorination; howDr.…”
Section: Introductionmentioning
confidence: 99%